Seloct the correct location on the solution path. Sean was given the following exponential equation to solve. \[ \begin{aligned} 7^{(2 x-2)} & =49^{(3 x+2)} \\ 7^{(2 x-2)} & =49^{(3 x+2)} \\ 7^{(2 x-2)} & =\left(7^{2}\right)^{(3 x+2)} \\ 7^{(2 x-2)} & =7^{(6 x+2)} \\ 2 x-2 & =6 x+2 \\ -4 x-2 & =2 \\ -4 x & =4 \\ x & =-1\end{aligned} \]
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the exponential equation \(7^{(2x-2)} = 49^{(3x+2)}\), the key insight is realizing that 49 can be rewritten as \(7^2\). This transformation allows us to express the equation entirely in terms of base 7, making it easier to equate the exponents. Through this process, Sean effectively streamlined his path to the solution, ultimately arriving at \(x = -1\). In the world of math, exponential equations are not just academic exercises; they're used in various real-world situations such as calculating population growth, radioactive decay, or even in finance for compound interest! Understanding how to manipulate exponentials provides valuable tools for interpreting and solving such applied problems.